Using participatory action research methods to create nutrition education that sustainably improves diet diversity through women's empowerment - Sly, Brittney Catherine, author; Weir, Tiffany, advisor; Melby, Chris, advisor; Cunningham-Sabo, Leslie, committee member; Leisz, Stephen, committee member (Colorado State University. Libraries, 2021)
Malnutrition is a major cause of morbidity and mortality for vulnerable sub-Saharan African populations, and despite decades-long efforts from global and regional organizations, the prevalence of malnutrition is not improving. Many programs fail to address the underlying causes of malnutrition within specific cultural and community contexts, particularly issues that contribute to malnutrition such as hygiene, agriculture, education, and poverty reduction. Therefore, there is a need for more sustainable, culturally inclusive, and targeted malnutrition remediation interventions that address the multifaceted issues involved with the rising numbers of malnourished people in sub-Saharan Africa. The purpose of this research was to develop a nutrition-sensitive agriculture intervention, aimed at sustainably increasing diet diversity and food security at the household level, in a rural Rwandan community, using Participatory Action Research (PAR) methods to empower women as peer educators. Small groups of women (n=42), divided into 6 groups of 7, collectively received agriculture trainings and nutrition education over the course of 16 weeks, along with the tools and support to start and maintain kitchen gardens. A large group session, using PAR methodology, was conducted to guide self-reflection and knowledge-assessment, while empowering women educators to spread information throughout their community. By coupling the intention of nutrition-sensitive agriculture with the empowering and inclusive methods of PAR, the goal was to provide the framework for establishing more sustainable nutrition-sensitive agriculture interventions, while encouraging the dissemination of information to the larger community. Collaborative community-based nutrition-sensitive agricultural interventions in rural, poor Rwandan populations can increase household diet diversity to encourage sustained change in dietary patterns for nutritional adequacy. Using kitchen gardens as the conduit for change, households can increase their consumption of home-grown vegetables, as well as other nutrient-dense foods. Additionally, employing PAR methods within the intervention design to enable participants to serve as active contributors and peer educators, enhanced women's empowerment and contributed to increased agency, as well as widespread information dissemination. However, more research concerning the systems that affect food availability and agricultural markets is needed to enact changes in food security, as well as more investigation into the ways in which empowerment influences the spread of information throughout a community.
Keywords: malnutrition; women's empowerment; participatory action research; diet diversity